Phenotypic profile of Aedes albopictus (skuse) exposed to pyrethroid-based mat vaporizers and underlying detoxification mechanisms: a statewide report in Selangor, Malaysia - Hizayu, Taib Azratul; Chen, Chee Dhang; Lau, Koon Weng; Wahid, Noor Azrizal; Tan, Tiong Kai; Lim, Yvonne Ai Lian; Azirun, Mohd Sofian; Low, Van Lun (Elsevier Ireland, 2022)
This study examines the biological efficacy of four mosquito mat vaporizers each containing different active ingredients: prallethrin with PBO, dimefluthrin, prallethrin, and d-allethrin. The glass chamber assay was used to evaluate their efficacy on Aedes albopictus (Skuse) (Diptera: Culicidae) from nine districts in Selangor, Malaysia. Aedes albopictus exhibited different knockdown rates, with 50% knockdown times, KT50, varying from 1.19 to 2.00 min, 1.22 to 2.20 min, 1.39 to 5.85 min, and 1.39 to 1.92 min for prallethrin with PBO, dimefluthrin, prallethrin and d-allethrin, respectively. In general, all populations of Ae. albopictus were completely knocked down after exposure to all active ingredients except Hulu Selangor population, which showed 96.00% knockdown against d-allethrin. On the contrary, mortality rates were observed from 84.00–100.00%, 84.00–100.00%, 90.67–100.00% and 90.67–100.00% in populations tested with prallethrin with PBO, dimefluthrin, prallethrin and d-allethrin, respectively. Moreover, significant correlations between mortality rates of prallethrin with PBO vs dimefluthrin (r = 0.836, P = 0.003), prallethrin with PBO vs prallethrin (r = 0.760, P = 0.011), and prallethrin vs d-allethrin (r = 0.694, P = 0.026) were also observed, suggesting cross-resistance among pyrethroids. d-allethrin was found to be high in insecticidal activity, followed by prallethrin, prallethrin with PBO, and dimefluthrin. In consistent with mortality due to insecticide exposure, elevated levels of enzyme activities were also demonstrated in Sabak Bernam, Hulu Selangor, Gombak, Petaling, Hulu Langat and Klang populations.